Phytochemical Study, Antimicrobial And Antiangiogenic Activities Of The Leaf Extracts Of Gynura Segetum - Seow , Lay Jing (2010)

(untitled)
Gynura segetum (daun dewa in Malay) is a herb from family compositae, reputed to possess various medicinal values. This plant is believed of value for treating cancer, diabetes, hypertension, inflammation and skin infection. The leaves of Gynura segetum were evaluated using quality control parameters, which include gravimetric, thin layer chromatographic (TLC) and high-performance liquid chromatographic (HPLC) analysis. The antimicrobial activity of different solvent extracts of leaves of Gynura segetum was evaluated using agar diffusion method. Ethyl acetate fraction exhibited the highest inhibitory effect and therefore further fractionation on this fraction was carried out. Fifteen new subfractions obtained were tested for antimicrobial activity and the MIC of the active subfractions was determined by tube dilution method.